Prevention of Diaper Dermatitis in Infants—a Literature Review. Issue 4 (29th May 2014) - Blume‐Peytavi, Ulrike; Hauser, Matthias; Lünnemann, Lena; Stamatas, Georgios N.; Kottner, Jan; Garcia Bartels, Natalie
Abstract Diaper dermatitis (DD) is one of the most common skin conditions in neonates and infants, with a peak between the ages of 9 and 12 months. Appropriate skin care practices that support skin barrier function and protect the buttocks skin from urine and feces are supposed to be effective in the prevention of DD. Despite many recommendations for parents and caregivers on proper diaper skin care, there is no up‐to‐date synthesis of the available evidence to develop recommendations for DD prevention practice. Therefore we performed a systematic literature review on the efficacy of nonmedical skin care practices on the diapered area of healthy, full‐term infants ages 0 to 24 months. We identified 13 studies covering skin care practices such as cleansing, bathing, and application of topical products. DD prevalence and incidence and physiologic skin parameters were used as efficacy parameters. The results of this review indicate that cleansing of the diaper area using baby wipes or water and a washcloth have comparable effects on diapered skin. Bathing with a liquid baby cleanser twice weekly seems comparable with water alone. The application of ointments containing zinc oxide or petrolatum with or without vitamin A seems to have comparable effects on DD severity. There seems to be no information on whether single skin care practices such as cleansing, bathing, and application of topical preparations can prevent DD. High‐quality randomized clinical trials are needed to show the effectiveness of skin care practices for controlling and preventing DD.